Lutein and zeaxanthin intake by Portuguese population: a Total Diet Study approach - Dias, Maria da Graça (2018)
Carotenoids are natural compounds that are present in fruits and vegetables, giving them different and appealing colors. There are many studies showing strong correlations between diets rich in carotenoids, both with the improvement of the immune system and with the reduction of the risk of some degenerative diseases such as cancer, cardiovascular diseases, cataract and macular degeneration.Fruits and vegetables are the main source of carotenoids. Aim: Evaluate the α-carotene, β-carotene, β-cryptoxanthin, lycopene, lutein and zeaxanthin content of soup samples representative of the Portuguese consumption.